A. AVLONI - ENLIGHTENER, TEACHER AND SCHOOL REFORMER - Даробов Рахмонжон Равшанович (Journals Park Publishing, 2023)
This article is devoted to the role of A. Avloni, a famous Uzbek writer, playwright, educator and teacher, who made a significant contribution to the development of pedagogical thought on the ideas of the socio-political movement Jadidism.
Keywords: heritage, enlightenment, upbringing, school, origin, Jadidism, development.